Analisis Nilai-Nilai Sosial dan Budaya Baritan dalam Peringatan Malam Satu Suro di Desa Tawangrejo Kecamatan Wonodadi Kabupaten Blitar - Syafira Hurin’in; Ikfi Khoulita (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The purpose of this study is to understand the process of implementing the baritan tradition in Tawangrejo Village and to identify the social and cultural values contained within the tradition. This research uses a qualitative approach with data collection techniques in the form of interviews and documentation. The results of the study show that the baritan tradition in Tawangrejo Village is held regularly every year, specifically on the eve of Satu Suro (the first day of the Javanese calendar). The tradition begins after the Maghrib prayer, marked by the local community bringing takir plontang, which are placed in the center as the community forms a circle around them. In addition, the baritan tradition contains both social and cultural values. The social values include compassion, responsibility, and social harmony. Meanwhile, the cultural values include the community’s behavior in relation to nature, interpersonal relationships within the society, and shared beliefs about desirable and undesirable actions.